Dual Agency Practices in Islamic Financial Institutions: A Fiqh Perspective - Shaharuddin, A.; Musa, A. A.; Mohamad Nawi, F. S.; Mohamed Ahmad, A. H.; Ab Mumin, A. M. (Universiti Sains Islam Malaysia, 2024)
Bay al-tawarruq is increasingly adopted by Malaysian Islamic financial institutions (IFIs) in creating both deposit and financing products. The contract involves sequences of trading between three parties namely client, IFIs and brokers. However, in order to simply the operation and to minimize client’s involvement, the actual trading are conducted between IFI and brokers only. IFI will act on behalf of the client and execute all trading transactions. The practice triggers fiqh issue because the IFI (as agent of client) will sell and purchase commodity to himself. The present article discusses the issue by assessing Muslim jurists’ view pertaining to dual agency practices. The article adopts juristic analysis method in which classical and contemporary scholars arguments are analysed before a preferred opinion (tarjih) is concluded. Understanding the issue is vital to avoid misunderstanding about the legality of Islamic financial products particularly products that used the organized bay’ al-tawarruq as the underlying contract.